Late phase of COVID‐19 pandemic in General Cardiology. A position paper of the ESC Council for Cardiology Practice. (25th June 2021) - Richter, Dimitrios; Guasti, Luigina; Koehler, Friedrich; Squizzato, Alessandro; Nistri, Stefano; Christodorescu, Ruxandra; Dievart, Francois; Gaudio, Giovanni; Asteggiano, Riccardo; Ferrini, Marc
Abstract: Cardiovascular (CV) engagement in coronavirus disease 2019 (COVID‐19) is a huge determinant of prognosis during the acute phase of the disease. However, little is known about the potential chronic implications of the late phase of COVID‐19 and about the appropriate approach to these patients. Heart failure, type 1 and type 2 myocardial infarction, arrhythmias, myocarditis, pulmonary fibrosis, and thrombosis have been shown to be related to severe acute respiratory syndrome coronavirus 2 infection, and a 'long COVID‐19' illness has been recognized with fatigue, chest pain, and dyspnoea among the most frequent symptoms reported after discharge from hospital. This paper focuses on some open questions that cardiologists are going to face during the next months in a general cardiology outpatient clinic, in particular how to evaluate a 'post‐COVID' patient during follow‐up of CV complications of the acute phase and how to manage new CV symptoms that could be the consequence, at least in part, of heart/vessels and/or lung involvement of the previous virus infection. Present symptoms and signs, history of previous CV disease (both preceding COVID‐19 and occurring during viral infection), and specific laboratory and imaging measurements during the acute phase may be of interest in focusing on how to approach the clinical evaluation of a post‐COVID patient and how to integrate in our standard of care the new information on COVID‐19, possibly in a multidisciplinary view. Dealing with the increased COVID‐associated CV risk burden and becoming acquainted with potential new e‐cardiology approaches aimed at integrating the cardiology practice are relevant new challenges brought by severe acute respiratory syndrome coronavirus 2 infection and its sequelae.